Hubungan Pengetahuan Gizi Ibu dengan Kejadian Underweight pada Balita - Marwah Ulfa; Rahmaniah; Riska Mayangsari; Nur Afia Amin; Rezal Hadi Basalamah (Universitas Sulawesi Barat, 2025)
Underweight is the most common condition of malnutrition in children aged five years and under and is caused by food intake that does not meet the physiological needs of the body. A lack of food intake can occur due to a lack of energy from staple food sources. Underweight in children under five years old can be caused by various factors, including a lack of knowledge about nutrition and health of parents, especially mothers and the socioeconomic situation of the family is one of the factors that determine the amount of food available in the family so that it also determines the nutritional status of the family. The purpose of this study was to determine the relationship between maternal nutritional knowledge and the incidence of underweight in toddlers in Bonde Utara Village, Pamboang District, Majene Regency. The type of research used is quantitative research with a cross sectional design and the sampling technique is purposive sampling. The analysis test used was chi-square test. The results showed a significant relationship between maternal nutrition knowledge (p=0.03 <0.05), an intensive nutrition education program is needed to reduce the prevalence of underweight in North Bonde Village.